Financial statement analysis - Foster, George (Prentice-Hall, 1986)
The book provides an intensive study of financial statement analysis, seeking to describe and explain: the demand and supply forces underlying the provision of financial statement data, the properties of numbers derived from financial statements, the key aspect of decisions that use financial statement information, and the features of the environment in which these decision are made. Each chapter contains much discussion of and many references to research on the topics covered. At the end of each chapter is a section titled "Some General Comments" that includes discussion of unresolved issues inexisting research, analysis of future research directions, or discussion of individual studies